Hesperidin Protects SH−SY5Y Neuronal Cells against High Glucose−Induced Apoptosis via Regulation of MAPK Signaling - Chaemoon Lim; Ao Xuan Zhen; Sungwoo Ok; Pincha Devage Sameera Madushan Fernando; Herath Mudiyanselage Udari Lakmini Herath; Mei Jing Piao; Kyoung Ah Kang; Jin Won Hyun (MDPI AG, 2022)
Neurodegenerative diseases are associated with neuronal cell death through apoptosis. Apoptosis is tightly associated with the overproduction of reactive oxygen species (ROS), and high glucose levels contribute to higher oxidative stress in diabetic patients. Hesperidin, a natural active compound, has been reported to scavenge free radicals. Only a few studies have explored the protective effects of hesperidin against high glucose−induced apoptosis in SH−SY5Y neuronal cells. Glucose stimulated neuronal cells to generate excessive ROS and caused DNA damage. In addition, glucose triggered endoplasmic reticulum stress and upregulated cytoplasmic as well as mitochondrial calcium levels. Hesperidin inhibited glucose−induced ROS production and mitigated the associated DNA damage and endoplasmic reticulum stress. The downregulation of antiapoptotic protein Bcl−2 following glucose treatment was reversed by a hesperidin treatment. Furthermore, hesperidin repressed the glucose−induced Bcl−2−associated X protein, cleaved caspase−9, and cleaved caspase−3. Hesperidin also suppressed the glucose−induced phosphorylation of extracellular signal−regulated kinase and c−Jun N−terminal kinase. The current results confirmed that hesperidin could protect neuronal cells against glucose−induced ROS. Mechanistically, hesperidin was shown to promote cell viability via attenuation of the mitogen−activated protein kinase signaling pathway.